Paddlewheel-Type Diruthenium(II) Naphthyridine Complex with Electron-Withdrawing Trifluoroacetate Ligands - Yusuke Kataoka; Nozomi Tada; Junya Omaki; Kanami Matsubara; Natsumi Yano; Makoto Handa (Chemistry)
A ligand exchange reaction between [Ru2(npc)2(O2CMe)2] (1; npc = 1,8-naphthyridine-2-carboxylate) and trifluoroacetic acid yielded the diruthenium naphthyridine complex with two trifluoroacetate ligands, [Ru2(npc)2(O2CCF3)2] (2), which was structurally characterized by electrospray ionization mass spectrometry, elemental analysis, infrared spectrum, and synchrotron single-crystal X-ray diffraction. The crystal structure of 2 adopts a paddlewheel-type structure in which two npc and two O2CCF3 ligands are coordinated in a cis-2:2 arrangement around the Ru2 core. The temperature-dependent magnetic susceptibility measurements indicated that 2 has (i) an S = 1 spin state for the Ru24+ core and (ii) a large D value of 243 cm−1; characteristic of paddlewheel-type Ru2 complexes. The cyclic voltammetry measurements indicated that 2 exhibited one reversible oxidation wave (E1/2 = 0.72 V vs. SCE) and two reduction waves (E1/2 = −0.67 and −1.10 V vs. SCE); which were clearly positively shifted when compared with those of 1. Additionally, the absorption spectrum of 2 displayed intense absorption bands in the visible region; attributed to metal-to-ligand charge transfer from the Ru2 core to the npc ligands; which were blue-shifted by approximately 70–100 nm when compared with those of 1. These distinct shifts in redox potentials and absorption bands originated from the strong electron-withdrawing effect of the O2CCF3 ligands in 2.